2013
DOI: 10.1097/scs.0b013e318286a0a3
|View full text |Cite
|
Sign up to set email alerts
|

Bone Repair is Influenced by Different Particle Sizes of Anorganic Bovine Bone Matrix

Abstract: Autogenous bone graft lead to the best result in terms of bone defect repair; ABBM of large and medium size granules are not totally reabsorbed at the observed period; ABBM of small size granules was more intensively reabsorbed and led to a greater osteoid tissue formation when compared to the medium and large ABBM granules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 20 publications
0
26
0
6
Order By: Relevance
“…On the other hand, higher mechanical stability can be achieved with tighter packing (Putzer, Coraça‐Huber, Wurm, Schmoelz, & Nogler, ). Furthermore, the granule size has important impact on material dissolution and resorption characteristics (Klüppel et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, higher mechanical stability can be achieved with tighter packing (Putzer, Coraça‐Huber, Wurm, Schmoelz, & Nogler, ). Furthermore, the granule size has important impact on material dissolution and resorption characteristics (Klüppel et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…34 A study in rabbit calvarial defects reported a greater amount of OD tissue and minimal fibrous tissue formation when allograft particles with size <450 lm were implanted instead of particles with larger size (up to 1000 lm). 18 Another study investigating the effect of particle size on the osseointegration of silicate-substituted calcium phosphates (Si-CaP) reported enhanced performance of particles with size in the range of 250-500 lm (36.5 6 2.3 area% new bone), while smaller particles (90-125 lm) promoted a less favorable healing outcome (30.4 6 3.5 area% new bone). 35 Similarly, our results show 22-30 area% new bone in the inner core of LV and HV grafts incorporating 105-500 lm allograft particles after 12 weeks, compared to 10-16 area% new bone for grafts with small particles > 105 lm.…”
mentioning
confidence: 99%
“…La condición estructural del injerto también ha sido vinculada a diferencias en la integración ósea, aunque la interface entre el injerto óseo y el lecho receptor no juega un rol importante cuando el injerto es de tipo autógeno (Netto et al, 2013a). Cuando materiales aloplásticos y heterógenos son utilizados, otros factores son protagonistas; Klüppel et al (2013) demostraron que el tamaño de partículas del relleno óseo de matriz bovina tienen influencia importante en el modelo de reparación ósea, donde partículas de gran tamaño presentan una reparación ósea altamente retardada. Otro factor relevante puede ser el vehículo de instalación del material (Buchaim et al, 2012); en esta investigación fue utilizado el suero fisiológico como elemento de transporte, lo cual puede influenciar positivamente en la regeneración ósea ya que otros modelos de transporte pueden influenciar negativamente en la regeneración de tejidos (Netto et al, 2013b).…”
Section: Discussionunclassified